A Baseline for Skeletal Investigations in Medaka (Oryzias latipes): The Effects of Rearing Density on the Postcranial Phenotype - Di Biagio, Claudia; Dellacqua, Zachary; Martini, Arianna; Huysseune, Ann; Scardi, Michele; Witten, Paul Eckhard; Boglione, Clara (Frontiers in Endocrinology, 2022)
Oryzias latipes is increasingly used as a model in biomedical skeletal research. The standard approach is to generate genetic variants with particular skeletal phenotypes which resemble skeletal diseases in humans. The proper diagnosis of skeletal variation is key for this type of research. However, even laboratory rearing conditions can alter skeletal phenotypes. The subject of this study is the link between skeletal phenotypes and rearing conditions. Thus, wildtype medaka were reared from hatching to an early juvenile stage at low (LD: 5 individuals/L), medium (MD: 15 individuals /L), and high (HD: 45 individuals /L) densities. The objectives of the study are: (I) provide a comprehensive overview of the skeletal elements in medaka; (II) evaluate the effects of rearing density on specific meristic counts and on the variability in type and incidence of skeletal anomalies; (III) define the best laboratory settings to obtain a skeletal reference for a sound evaluation of future experimental conditions; (IV) contribute to elucidating the structural and cellular changes related to the onset of skeletal anomalies. The results from this study reveal that rearing densities greater than 5 medaka/L reduce the animals’ growth. This reduction is related to decreased mineralization of dermal (fin rays) and perichondral (fin supporting elements) bone. Furthermore, high density increases anomalies affecting the caudal fin endoskeleton and dermal rays, and the preural vertebral centra. A series of static observations on Alizarin red S-whole mount stained preural fusions provide insights into the etiology of centra fusion. The fusion of preural centra involves the ectopic formation of bony bridges over the intact intervertebral ligament. An apparent consequence is the degradation of the intervertebral ligaments and the remodeling and reshaping of the fused vertebral centra into a biconoid-shaped centrum.